The expanding spectrum of clinically-distinctive, immunotherapy-responsive autoimmune encephalopathies. - Irani, SR; Vincent, A (2012)
The autoimmune encephalopathies are a group of conditions that are associated with autoantibodies against surface neuronal proteins, which are likely to mediate the disease. They are established as a frequent cause of encephalitis. Characteristic clinical features in individual patients often allow the specificity of the underlying antibody to be confidently predicted. Antibodies against the VGKC-complex, mainly LGI1(leucine-rich glioma-inactivated 1), CASPR2 (contactin-associated protein 2), and contactin-2, and NMDA (N-methyl, D-aspartate) -receptor are the most frequently established serological associations. In the minority of cases, an underlying tumour can be responsible. Early administration of immunotherapies, and tumour removal, where it is relevant, offer the greatest chance of improvement. Prolonged courses of immunotherapies may be required, and clinical improvements often correlate well with the antibody levels. In the present article, we have summarised recent developments in the clinical and laboratory findings within this rapidly expanding field.